Retrospective Analysis of the Application of the ECBs Key Interest Rates to the Macroeconomic Indicators of the CEMAC - Oumbe, Tekam; Nguekam, Chouafi; Kamta, Takoulac; Ongo (Asian Journal of Economic Modelling, 2020)
This article focuses on a comparative analysis of the responses of the CEMAC macroeconomic variables to the shocks of the key interest rates fixed by the BEAC and the ECB. To do this, we used a panel for the period 2011-2018. Thanks to the analysis of the simulations made possible by the SVAR estimate, we find that the CEMAC macroeconomic variables namely real GDP, private investment and inflation respond positively to the shocks of the ECB lending marginal rate, unlike that of the BEAC. In addition, the economic activity and private investment of the CEMAC countries are sensitive to the shocks of the deposit facility rate of the ECB and not to that of the BEAC. Furthermore, the application of the BEAC deposit facility rate only stimulates inflation in the CEMAC. The CEMAC macroeconomic variables have similar responses both in shock of the BEAC TIAO and that of the ECB. Therefore, it would be advantageous for the monetary authorities of the BEAC to apply the marginal lending facility rate and the deposit facility rate of the ECB; because it is a pledge of economic prosperity of the CEMAC countries. However, the success of this monetary policy also requires the support of public authorities.